MAL and TMEM220 are novel DNA methylation markers in human gastric cancer. (2nd January 2017) - Choi, Boram; Han, Tae-Su; Min, Jimin; Hur, Keun; Lee, Sun-Min; Lee, Hyuk-Joon; Kim, Young-Joon; Yang, Han-Kwang
Abstract: Context: Gastric cancer (GC) is the fourth most common cause of cancer-related deaths worldwide. Objective: To determine the mRNA-expression of the MAL, TMEM220, MMP28, IL-19 and HOPX genes and analyse the methylation statuses of MAL and TMEM220 . Materials and methods: Gene-expression levels were analysed in 10 GC cell lines and 30 matched pairs of GC and normal mucosa (NM) gastric tissue specimens in real-time reverse-transcriptase polymerase chain reactions. Gene methylation was evaluated by bisulphite sequencing. Detailed gene-methylation patterns were confirmed by pyrosequencing analysis. Results: MAL, TMEM220, MMP28 and IL-19 were significantly down-regulated in GC cell lines and GC tissues compared to NM tissues. MAL and TMEM220 were highly methylated in GC tissues, and methylation inversely correlated with expression. MAL and TMEM220 expression were restored by treatment with 5-aza-2′-deoxycytidine. MAL and TMEM220 were specifically methylated and were down-regulated in human GC. Discussion and conclusion: These loci may serve as novel methylation markers for patients with GC.